2017
DOI: 10.18632/oncotarget.21366
|View full text |Cite
|
Sign up to set email alerts
|

IGF1gene polymorphisms associated with diabetic retinopathy risk in Chinese Han population

Abstract: ObjectiveThis study aimed to explore the association of insulin-like growth factor 1 gene (IGF1) polymorphisms with diabetic retinopathy (DR) in a Chinese Han population.MethodsPolymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was used for genotyping. Genotype frequencies were compared by chi-square test. Odds ratio (OR) with 95% confidence interval (95%CI) was calculated to express the risk intensity of DR. Linkage disequilibrium between IGF1 polymorphisms was analyzed by Haploview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…Dotta et al reported that the rs35767GG genotype exhibited circulating concentrations of IGF1 and lower insulin sensitivity in Europeans [11]. However, Zhang et al found that the A allele of rs35767 contributed to the risk of developing T2DM in a Chinese Han population [25]. Presently, we did not find evidence of an association between rs35767 and T2DM.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Dotta et al reported that the rs35767GG genotype exhibited circulating concentrations of IGF1 and lower insulin sensitivity in Europeans [11]. However, Zhang et al found that the A allele of rs35767 contributed to the risk of developing T2DM in a Chinese Han population [25]. Presently, we did not find evidence of an association between rs35767 and T2DM.…”
Section: Discussioncontrasting
confidence: 87%
“…In addition to the indirect role of JAZF1, IGF1, and IGF2BP2 in insulin resistance involving lipid metabolism, the three proteins can also have direct effects on glucose metabolism [5,16,19]. The genes encoding these proteins, as well as their SNPs, have been associated with T2DM and metabolic traits [6,11,[20][21][22][23][24][25][26]. For example, Long et al reported that rs6769511C in IGF2BP2 was associated with the risk of T2DM in African Americans [22].…”
Section: Ivyspringmentioning
confidence: 99%
“…[25] According to existing documents, there are some functional polymorphisms in IGF-1 gene which could influence the transcriptional activity and protein production, like rs35767, rs5742714, and rs972936. [1921] Moreover, a series of studies have demonstrated that these three polymorphisms were involved in various human diseases. For instance, Marini et al reported that the individuals carrying rs35767 T allele showed low risk of anemia compared with C allele.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al suggested that IGF1 rs35767 polymorphism might contribute to the risk of diabetic retinopathy through regulating serum concentration of IGF1 in Chinese Han population. [19] Cao et al reported that the genetic variants of rs5742714 polymorphism showed obvious association with IGF1 serum level, moreover, rs5742714 may be a genetic predictor of susceptibility and prognosis for renal cell carcinoma among Chinese Han population. [20] Rs972936 also holds the capacity to regulate human diseases via influencing circulating levels of IGF-1 .…”
Section: Introductionmentioning
confidence: 99%
“…The SNP rs35767 is known to contribute to the development of diabetes in various population. A study showed TT genotype of rs35767 increased 1.92 fold and 1.77 fold of risk for T2DM and diabetic retinopathy in the Chinese Han population, respectively [21]. Besides, CC genotype of rs7136446 had higher body mass index and body fat percentage than TT and CT genotypes [22] but lacking evidence on other metabolic traits [23].…”
mentioning
confidence: 99%